Penurunan Intensitas Nyeri Gout Arthritis Melalui Kombinasi Kompres Jahe Hangat dan Aromaterapi Uap Minyak Kayu Putih - Ardany, Ravika Putri; Widayati, Dhina; Setyorini, Dwi (STIKES dan AKZI Karya Husada Kediri, 2024)
Gout arthritis pain is caused by a buildup of excess uric acid levels in the joints. Non-pharmacological interventions that can be applied are a combination of warm ginger compresses and eucalyptus oil steam aromatherapy. The aim of the study was to determine the effect of a combination of warm ginger compresses and eucalyptus oil vapor therapy on the intensity of Gout Arthritis pain. The research design uses Pre-Experimental (One group pre-post test design). The sample size is 24 respondents using purposive sampling. The results showed that before the intervention, almost all respondents (87.5%) had moderate criteria for Gout Arthritis pain intensity. Then after the intervention, the intensity of Gout Arthritis pain in the majority of respondents (54.2%) was in the mild criteria. Analysis with the Wilcoxon test (p-value 0.001 <α 0.05) showed that the combination of warm ginger compresses and eucalyptus oil steam aromatherapy had an effect on the intensity of gout arthritis pain.The combination of warm ginger compresses and eucalyptus oil vapor therapy can reduce the pain of Gout Arthritis patients due to increased feelings of relaxation and decreased muscle tension and vascular vasodilation due to the release of endorphins. It is recommended that gout sufferers do this non-pharmacological therapy to reduce pain levels.